Seguro e risco moral: o seguro de responsabilidade civil dos administradores (directors & officers liability insurance) e as ferramentas regulatórias para mitigar o risco moral no contexto corporativo - Gonçalves Filho, Péricles (2019)
Insurance is a key institution for contemporary societies. Traditionally analyzed and conceived as a contract, insurance can be analyzed from other perspectives, including that which sees it as an instrument capable of performing a regulatory function similar to that performed by the State, being, in this case, seen as a regulatory intermediary that seeks to shape risk behavior in order to avoid or reduce insured losses. In order to make it possible to perform this function, the foreign literature analyzed in this paper states that insurance has tools similar to the regulatory tools that the State uses to carry out the regulation function, and, when handling these tools, insurers could mitigate the problem of moral hazard that significantly affects the insurance industry. The present work aims to analyze this literature in order to identify which are these regulatory tools and if they could really mitigate the moral hazard in the context of the insurance relation. More specifically, this paper will analyze civil directors’ and officers’ liability insurance, which aims to protect the assets of company managers from possible liability as a result of acts practiced in the exercise of their functions. The hypothesis, formulated here, is that D & O insurance in Brazil has tools to mitigate the moral hazard that arises from the moment a policy is acquired. The choice of D & O insurance as a case study stems from the fact that Brazil, over recent years and similar to what occurs in several other developed countries, has been intensifying the rules of accountability of company managers, becoming more and more noticeable the concern of the legislator with the reflections of the conduct of these administrators, so that it becomes fundamental to analyze whether D & O insurance really has the means to avoid moral hazard. The justification for the study is that insurance is spread throughout society, playing a fundamental role in the life of people, in the daily life of corporations and impacting the state itself, and it is fundamental to analyze the literature that sees insurance as an instrument of risk control, and tools to mitigate moral hazard, especially in the corporate context in which D & O insurance operates.